2012
DOI: 10.1039/c1ob06776a
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Payne/Meinwald versus Meinwald rearrangements on the α-hydroxy- or α-silyloxy-spiro epoxide skeleton

Abstract: Under Lewis acid activation, the new α-hydroxy-spiro epoxide scaffold 1a underwent an original tandem Payne/Meinwald rearrangement affording the cyclopentyl hydroxymethylketone 6 in a stereospecific manner, while a Meinwald-type epoxide rearrangement occurred when the derived α-trimethylsilyloxy-spiro epoxide 2a was treated with MABR, yielding stereoselectively the cyclohexane carbaldehyde 9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Isomeric MBO epoxides are possible in the chamber and field studies (Figure S3 of the Supporting Information, proposed oxidation pathway), and consistent with this possibility, three peaks are resolved in organosulfate EICs C2 and C3. Because the reactive uptake of pure (3,3-dimethyloxiran-2-yl)­methanol should initially yield two sulfate isomers, the presence of three isomeric esters in C1 likely suggests either an initial Payne rearrangement , of the epoxide on reactive uptake or intramolecular transesterification , promoted by the acidic seed aerosol may be involved in reactive uptake. Differences in the pattern of peak intensities of the EIC traces in Figure are expected because isomer ratios from aerosol generated under different conditions are not anticipated to be identical.…”
Section: Resultsmentioning
confidence: 99%
“…Isomeric MBO epoxides are possible in the chamber and field studies (Figure S3 of the Supporting Information, proposed oxidation pathway), and consistent with this possibility, three peaks are resolved in organosulfate EICs C2 and C3. Because the reactive uptake of pure (3,3-dimethyloxiran-2-yl)­methanol should initially yield two sulfate isomers, the presence of three isomeric esters in C1 likely suggests either an initial Payne rearrangement , of the epoxide on reactive uptake or intramolecular transesterification , promoted by the acidic seed aerosol may be involved in reactive uptake. Differences in the pattern of peak intensities of the EIC traces in Figure are expected because isomer ratios from aerosol generated under different conditions are not anticipated to be identical.…”
Section: Resultsmentioning
confidence: 99%
“…The α-hydroxy oxirane structural motif may shed light on the stereochemistry as illustrated in Figure 6. The C1 OH can interact with the incipient C2 carbonium ion in the transition state, which is similar to that of an acid-catalyzed Payne rearrangement, 111 and the C4 hydroxy substituent can interact with the oxirane oxygen through hydrogen bonds with or without an intervening water molecule. This transition state could direct the approach of sulfate and result in predominance of either retention or inversion of optical configuration at C2.…”
Section: Reaction Mechanism and Kineticsmentioning
confidence: 94%
“…In 2012, Gosselin et al reported the Lewis acid-induced tandem Payne/Meinwald rearrangement of a-hydroxyl-spiro epoxide 121, which gave ketone 123 as the single product in the presence of Yb(OTf) 3 , BF 3 OEt 2 , or SnCl 4 (equation 12). 95 This tandem procedure began with the acid-induced Payne rearrangement of substrate 121, followed by a ring contraction of the resulting intermediate 122 to furnish stereospecifically the ketone 123. …”
Section: Side Reactionmentioning
confidence: 99%